Impact of COVID-19 Pandemic on Air Pollution in Poland Based on Surface Measurements and Satellite Data - Mikalai Filonchyk; Volha Hurynovich; Haowen Yan (Aerosol and Air Quality Research)
Abstract Since its first detection in December 2019 in the Chinese city of Wuhan, the virus has become a global pandemic within just three months. The Polish government declared a state of emergency on March 14, 2020, which was connected with the adoption of a number of measures aimed to prevent the spread of the virus. These restrictive measures have led to improvements in air quality throughout the country. Therefore, evaluation of the reduction in anthropogenic emissions due to COVID-19 and related government measures to constrain its spread is crucial to define its impact on air pollution. During this study, aerosol optical depth (AOD) observations from the Moderate Resolution Imaging Spectroradiometer (MODIS) were used along with tropospheric NO2 and SO2 vertical column densities from TROPOspheric Monitoring Instrument (TROPOMI). The data on ground-based concentrations of pollutants (PM2.5, PM10, NO2 and SO2) obtained from air quality monitoring stations were also considered to assess changes in aerosols and air pollutants connected with the cessation of various kinds of anthropogenic and industrial activities due to preventive measures for COVID-19. In large cities of the country, the concentrations of PM2.5, PM10 and NO2 were reduced in the range from −5.1% to −35.5%, from −8.3% to −33.1% and from −0.4% to −18.8%. In addition, satellite data for NO2 and SO2 also indicate a decrease in concentration across the country by −10.8% and −25.6% during the COVID-19 restrictions period. The lockdown events may play a vital role as a potential solution to reduce air pollution in future as it may not be uncommon for governments to introduce deliberately selective hotspot lockdowns to control pollution levels.